KARAKTERISTIK KECEPATAN NYALA DAN KONSENTRASI ION PADA PEMBAKARAN PREMIXED BUTANA - Muh Nurkoyim Kustanto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Research on premixed butane combustion has been carried out, to determine the characteristics of flame velocity and ion concentration. The research was carried out by combining premixed butane mixture in a cylindrical combustion chamber measuring 108 mm in diameter and 170 mm in length. The premixed butane air mixture is set at the equivalent composition ratio  = 0.8; 0.9; 1.0; 1.1; 1,2. The results showed that the highest flame speed was equivalent to a ratio of 1.1, which was 198 cm / s whereas the highest radical concentration indicated by the voltage on the ion sensor system is equivalent to a ratio of 1.1, which is 5.5 volts. Keywords: butane, flame velocity, radical concentration, premixed combustion